PEMETAAN MUTU AKREDITASI PAUD DAN PNF di KABUPATEN KULONPROGO, YOGYAKARTA - ROYATI ILYAS (Balitbangda Provinsi Jambi, 2021)
Accreditation is one of the governments to improve the quality of education. Likewise, to ensure the quality of education at the PAUD and PNF levels, the government held an accreditation program. However, it still has issues that need to be resolved. This study aims to identify and describe the problems of accreditation and quality mapping in the Education Office of Kulonprogo Regency. This research uses a qualitative approach and type of case study research. Based on the results of this research, in mapping the quality of accreditation in PAUD and PNF in Kulonprogo Regency, the first activity carried out was to conduct a quality mapping analysis of each institution. And the results show that the average standard kindergarten, KB, Pos PAUD, LPK and PKBM institutions that must be supervised strictly is the standard of financing. After conducting the analysis, a workshop was conducted with the Dikpora and all PAUD and PNF heads. Keywords: Quality mapping, accreditation, PAUD, PNF.